LU-10M LINAC synchronization system - Boriskin, V.N.; Momot, V.A.; Churikov, V.V.; Solodovnikov, V.I.; Zaitsev, E.I. (Вопросы атомной науки и техники, 2022)
The synchronization system is based on STM32F407VG and DP83848. The system generates pulses with a fre-quency of 1 to 600 Hz, a length of up to 2500 ns to synchronize the operation of the klystron modulator, master oscillator, source modulator, control equipment of LINAC. The setting of the delay of the synchronization pulses is adjustable from 0.01 to 20 μs. Synchronization system control is implemented via USB or Ethernet network via TCP/IP protocol. Implemented a set of applications for the organization of system management and monitoring of LINAC, compatible with Windows XP/7/10. Система синхронізації розроблена на основі STM32F407VG та DP83848. Система формує імпульси частотою від 1 до 600 Гц, довжиною до 2500 нс для синхронізації роботи модулятора клістрона, задающого генератора, модулятора джерела, контрольної апаратури ЛПЕ. Установка затримки імпульсів синхронізації регулюється від 0,01 до 20 мкс. Керування системою синхронізації реалізовано за допомогою USB або Ethernet-мережі за протоколом TCP/IP. Реалізований комплекс додатків для організації керування системою та спостереження за роботою ЛПЕ, сумісний з ОС Windows XP/7/10. Система синхронизации разработана на основе STM32F407VG и DP83848. Система формирует импульсы частотой от 1 до 600 Гц, длиной до 2500 нс для синхронизации работы модулятора клистрона, задающего генератора, модулятора источника, контрольной аппаратуры ЛУЭ. Установка задержки импульсов синхронизации регулируется от 0,01 до 20 мкс. Управление системой синхронизации реализовано с помощью USB или Ethernet-сети по протоколу TCP/IP. Реализован комплекс приложений для организации управления системой и наблюдения за работой ЛУЭ, совместимый с ОС Windows XP/7/10.